Promotion Effect of CaO Modification on Mesoporous Al2O3-Supported Ni Catalysts for CO2 Methanation - Wen Yang; Yanyan Feng; Wei Chu (International Journal of Chemical Engineering)
The catalysts Ni/Al2O3 and CaO modified Ni/Al2O3 were prepared by impregnation method and applied for methanation of CO2. The catalysts were characterized by N2 adsorption/desorption, temperature-programmed reduction of H2 (H2-TPR), X-ray diffraction (XRD), and temperature-programmed desorption of CO2 and H2 (CO2-TPD and H2-TPD) techniques, respectively. TPR and XRD results indicated that CaO can effectively restrain the growth of NiO nanoparticles, improve the dispersion of NiO, and weaken the interaction between NiO and Al2O3. CO2-TPD and H2-TPD results suggested that CaO can change the environment surrounding of CO2 and H2 adsorption and thus the reactants on the Ni atoms can be activated more easily. The modified Ni/Al2O3 showed better catalytic activity than pure Ni/Al2O3. Ni/CaO-Al2O3 showed high CO2 conversion especially at low temperatures compared to Ni/Al2O3, and the selectivity to CH4 was very close to 1. The high CO2 conversion over Ni/CaO-Al2O3 was mainly caused by the surface coverage by CO2-derived species on CaO-Al2O3 surface.